Pelaksanaan Perjanjian Kerjasama Antara Rumah Sakit Umum Daerah Palembang Bari dengan PT. Asuransi Inhealth Kesehatan - Apriadi, Ruly; Sa, Romli; Hayatuddin, Khalisah; Mahfuz, Abdul Latif (Fakultas Syariah INSURI Ponorogo, 2023)
The purpose of this paper This research focuses on the implementation of cooperation between Palembang BARI Regional General Hospital (RSUD) and PT. Health Inhealth Insurance in the context of health services and the provision of drugs for insurance participants. Normative legal research methods with e-explanatory approach are used, with a legal approach and a concept approach to investigate how cooperation agreements are implemented and what obstacles are faced. Secondary data are taken as sources of information and analyzed using qualitative data analysis techniques. The results show that the cooperation agreement has fulfilled the provisions in Article 1320 of the Civil Code, but there are several obstacles in its implementation. These obstacles include the difficulty of changing the standard clauses of the agreement, the lack of specific regulations on the implementation of cooperation agreements, and the lack of online integration between the hospital system and PT. Health Inhealth Insurance. This research hopes to help improve the quality of cooperation between health care facilities and insurance companies.